Phylogeny of the damselfishes (Pomacentridae) and patterns of asymmetrical diversification in body size and feeding ecology. - Charlene L McCord (Public Library of Science (PLoS), 2021)
The damselfishes (family Pomacentridae) inhabit near-shore communities in tropical and temperature oceans as one of the major lineages in coral reef fish assemblages. Our understanding of their evolutionary ecology, morphology and function has often been advanced by increasingly detailed and accurate molecular phylogenies. Here we present the next stage of multi-locus, molecular phylogenetics for the group based on analysis of 12 nuclear and mitochondrial gene sequences from 345 of the 422 damselfishes. The resulting well-resolved phylogeny helps to address several important questions about higher-level damselfish relationships, their evolutionary history and patterns of divergence. A time-calibrated phylogenetic tree yields a root age for the family of 55.5 mya, refines the age of origin for a number of diverse genera, and shows that ecological changes during the Eocene-Oligocene transition provided opportunities for damselfish diversification. We explored the idea that body size extremes have evolved repeatedly among the Pomacentridae, and demonstrate that large and small body sizes have evolved independently at least 40 times and with asymmetric rates of transition among size classes. We tested the hypothesis that transitions among dietary ecotypes (benthic herbivory, pelagic planktivory and intermediate omnivory) are asymmetric, with higher transition rates from intermediate omnivory to either planktivory or herbivory. Using multistate hidden-state speciation and extinction models, we found that both body size and dietary ecotype are significantly associated with patterns of diversification across the damselfishes, and that the highest rates of net diversification are associated with medium body size and pelagic planktivory. We also conclude that the pattern of evolutionary diversification in feeding ecology, with frequent and asymmetrical transitions between feeding ecotypes, is largely restricted to the subfamily Pomacentrinae in the Indo-West Pacific. Trait diversification patterns for damselfishes across a fully resolved phylogeny challenge many recent general conclusions about the evolution of reef fishes.